The Implications of The Sino-Indian Competition on The Regional Security System of South and Southeast Asia in The Context of Globalization - Mohammed , Mona Hani (Dirasat: Human and Social Sciences, 2023)
Objectives: The study aims to demonstrate the implications of the competition between China and India on the regional security system of South and Southeast Asia in the context of globalization. Methods: The nature of the subject of this study calls for reliance on the descriptive, historical and the analytical approach to provide clarity. Results: The study yielded a set of results and recommendations, with the most significant one being that the presence of rising regional powers, such as China and India, which are geographically contiguous and competitive, hinders the establishment of a stable regional security system dominated by either of these powers. Moreover, in the context of globalization, particularly in its economic dimension, these powers are driven by economic considerations, which, in turn, influences the means and strategies employed to pursue their interests. Additionally, smaller countries in this system leverage this competition to their advantage, seeking to secure the maximum amount of economic support and investment. These countries enjoy freedom of movement and maneuver without committing to alliances with either side. Conclusions: The study’s importance lies in its focus on the South and Southeast Asia region, specifically the interactions between China and India as being two rising powers and Asian giants. The study recommends the need to strengthen the various channels of dialogue and communication between China and India in order to settle outstanding issues and work towards establishing a stable regional security system.